Pesan Komunikasi Islam dalam Tradisi Bondang dan Implikasinya terhadap Keagamaan Masyarakat Muslim di Kabupaten Asahan - Kiki Rahmayani Hasibuan; Rubino Rubino; Mailin Mailin (PERSPEKTIF, 2022)
The purpose of this study was to analyze the implications of Islamic communication messages and the efforts made by the community to preserve Bondang Tradition in the community in Asahan Regency. This research is a qualitative research, more precisely a research strategy that tries to describe the item or subject under study. Therefore, in this review, to obtain information, the researcher used a subjective technique. The results of the study indicate that there are three Islamic Communication Messages contained in the Bondang Cultural tradition in Silo Lama Village, Silau Laut District, Asahan Regency, including messages of faith, messages of sharia and muamalah, and moral messages. The implications of Islamic Communication Messages contained in the Bondang Cultural tradition in Silo Lama Village, Silau Laut District, Asahan Regency, there are three including messages of faith, messages of sharia and muamalah, as well as moral messages that are actually practiced by people in their daily lives. Community efforts in preserving the Bondang Tradition of Asahan Regency include some of the community trying to tell the history of Bondang Tradition to their children and relatives as a tradition that reminds how their village was opened and can be occupied by Muslim communities like them until now.